Pengaruh Ketebalan dan Suhu Pengeringan Terhadap Karakter Fisik dan Sensoris Buah Naga Merah Kering - Dinda Mar’atuzzahwa; I Made Supartha Utama; I Putu Surya Wirawan (Jurnal BETA (Biosistem dan Teknik Pertanian), 2023)
Red dragon fruit (Hylocereus polyrhizus) is a type of tropical plant that can adapt to changes in weather and fruit production every season is very abundant. Drying is the process of reducing the moisture content in the material so that the material can be stored relatively long. This study was conducted to find out the effect of drying thickness and temperature on the physical characteristics and sensorical characteristics of dried red dragon fruit. This research method used a Randomized Block Design (RBD) with 2 factors namely drying temperature (60 °C, 70 °C and 80 °C) and fruit thickness (0.5 cm, 0.75 cm, and 1 cm). Each treatment combination unit consists of 9 slices of fresh red dragon fruit and each combination of treatment is repeated 3 times. Parameters observed include water content, water activity, texture, yield, color difference, total dissolved solids, and organoleptic tests. The data of this study was tested with analysis of variance, if significant differences were found, followed by Duncan's testing. The results of the study provided the results that the thickness and drying temperature exerted a noticeable influence on the physical and sensory character of dried red dragon fruit. The treatment of a thickness of 0.75 cm and a drying temperature of 80 oC exerts a significant effect on the yield of dried dragon fruit. best with a water content value of 13.75 %, water activity of 0.65, texture of 36.48, yield of 16.28 %, color difference of 23.03, total sugar of 8.30 oBrix, and organoleptic test value of 3.44, aroma of 3.40, texture of 4.84, taste of 4.84, and favorite level combination value of 4.84.